Survival of Business by Turning Towards Rural Markets - Kumar, Sandeep; Shrotriya, Sugandha (Journal of Commerce and Trade, 2009)
A recession is a decline in a country’s gross domestic product (GDP) growth for two or more consecutive quarters of a year. A recession is also preceded by several quarters of slowing down. An economy which grows over a period of time tends to slow down the growth as a part of the normal economic cycle. An economy typically expands for 6-10 years and tends to go into a recession for about six months to 2 years. A recession normally takes place when consumers lose confidence in the growth of the economy and spend less. This leads to a decreased demand for goods and services, which in turn leads to a decrease in production, lay-offs and a sharp rise in unemployment. Investors spend less as they fear stocks values will fall and thus stock markets fall on negative sentiment. Economic recession hit the urban pockets badly and forced companies to train their guns on rural India, which was witnessing a major change in its aspiration and lifestyles and even had an income that translated into increasing volumes. Certainly, rural marketing holds the key to success of FMCG companies, which are desperate to find ways out to gain deeper penetration. Not just the rural population is numerically large; it is growing richer by the day. Of late, there has been a phenomenal improvement in rural incomes and rural spending power.